2024
DOI: 10.1021/acsnano.3c11960
|View full text |Cite
|
Sign up to set email alerts
|

A Cancer Nanovaccine Based on an FeAl-Layered Double Hydroxide Framework for Reactive Oxygen Species-Augmented Metalloimmunotherapy

Mengyu Chang,
Man Wang,
Bin Liu
et al.

Abstract: The complexity and heterogeneity of individual tumors have hindered the efficacy of existing therapeutic cancer vaccines, sparking intensive interest in the development of more effective in situ vaccines. Herein, we introduce a cancer nanovaccine for reactive oxygen species-augmented metalloimmunotherapy in which FeAl-layered double hydroxide (LDH) is used as a delivery vehicle with dihydroartemisinin (DHA) as cargo. The LDH framework is acid-labile and can be degraded in the tumor microenvironment, releasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…It is typically accompanied by the release of numerous inflammatory molecules and cellular contents such as lactate dehydrogenase (LDH). The degradation of LDH in the tumor microenvironment can contribute to cancer cell apoptosis and immunogenic cell death by exacerbating oxidative stress within the tumor . As shown in Figure c, the PDI+Light group significantly stimulated the release of LDH, resulting in much higher levels of LDH in the cellular supernatants compared to the control groups.…”
mentioning
confidence: 94%
“…It is typically accompanied by the release of numerous inflammatory molecules and cellular contents such as lactate dehydrogenase (LDH). The degradation of LDH in the tumor microenvironment can contribute to cancer cell apoptosis and immunogenic cell death by exacerbating oxidative stress within the tumor . As shown in Figure c, the PDI+Light group significantly stimulated the release of LDH, resulting in much higher levels of LDH in the cellular supernatants compared to the control groups.…”
mentioning
confidence: 94%
“…This unique iron metabolism is also linked to stemness maintenance. , Previous studies have revealed that the iron addiction of CSCs also makes them vulnerable to ferroptosis inducers, which makes ferroptosis a potential process to combat CSCs. Arising types of iron-based ferroptosis inducers have been developed to trigger an intracellular Fenton reaction, including ion oxides, LDH, or FeP . Several strategies having been proposed to promote the limited Fenton catalytic efficiency, such as introducing reductive components (EGCG) to reduce Fe 3+ to Fe 2+ .…”
mentioning
confidence: 99%